Pertanggungjawaban Pidana Bagi Pelaku Tindak Pidana Pencurian Data Nasabah Perbankan Dengan Metode Skimming Di Tinjau Menurut Undang-Undang Informasi Dan Transaksi Elektronik - Surya Ari Wibowo; Alvi Syahrin; Mahmud Mulyadi; sunarmi sunarmi (Iuris Studia: Jurnal Kajian Hukum, 2021)
This research is focused on one of the cyber crime in the banking sector in the form of a criminal act of theft of bank customer data by skimming method in which skimming is an act of theft of debit or credit card information by accessing automated teller machines and copying information contained on the magnetic stripe of cards debit or credit owned by the customer (victim) illegally to have control over the customer's (victim) account. The problems raised in this study are how the perpetrators 'actions can be categorized as criminal acts of theft of bank customer data using the skimming method, and how criminal liability for the perpetrators of the theft of bank customers' data theft by the skimming method. To find answers to these problems, this study uses a type of normative legal research that is descriptive analytical, where normative legal research uses secondary data as the main data using data collection techniques carried out by library research, and data analysis uses qualitative data analysis methods. The offender's actions that can be categorized as a crime of theft of banking customer data using the skimming method, namely the perpetrator in the crime of theft of banking customer data using the skimming method using tools such as skimmers, keypads, surveillance cameras, and fake debit cards, then transferring customer data that has been stolen. the perpetrator's fake debit card and the perpetrator then uses a fake debit card that has been filled in with the customer's data and drains the customer's savings in the savings. Criminal liability for perpetrators of criminal acts of theft of banking customer data using the skimming method if viewed based on the Denpasar District Court Decision Number 262/Pid.Sus/2017/PN. Dps and Denpasar District Court Decision Number 573/Pid.Sus/2018/PN. Dps above, it can be concluded that before the defendant takes responsibility for the criminal act he committed, in addition to having to see and examine the evidence presented before the trial, it must also be seen that the defendant's ability to be responsible, the defendant's fault, and the absence of reasons. a criminal offense for an act committed by the defendant